Narrative Literacy and Digital Storytelling in Indonesian Language Education: A Humanistic Framework for Values, Identity, and Critical Digital Literacies - Utami, Zathu Restie; Kurniawan, Agus (Asosiasi Asesmen Pendidikan (AAP), 2026)
Humanities-centered education positions language learning as a space where identity, values, and meaning are negotiated through narrative. In Indonesia, persistent challenges in reading performance, alongside rapid digital transformation, create an urgent need for pedagogy that strengthens narrative literacy while cultivating critical digital literacies (OECD, 2023a; OECD, 2023b). This article develops a humanistic framework for integrating digital storytelling (DST) into Indonesian language education to support (a) narrative competence, (b) value formation and cultural identity, and (c) ethical, critical, and creative participation in digital culture (UNESCO, 2024; Katadata & Sibercakap Digital, 2023). Using a scoping review approach, literature from 2021–2025 on DST, multimodal composing, multiliteracies pedagogy, and narrative inquiry is synthesized (Jiang & Hafner, 2024; Veyis et al., 2025). The synthesis highlights mechanisms through which DST contributes to writing development and engagement (Ajabshir, 2024; Meletiadou, 2022), and it foregrounds GenAI-era risks and equity issues that demand critical ethical literacy (Kim et al., 2025; Rapanta et al., 2025). The paper proposes design principles, an instructional sequence, assessment indicators, and safeguards to guide Indonesian language teachers.